Charakterystyka morfologiczna i sprawności fizycznej 7 - letnich dzieci uczęszczających do Zespołu Szkół nr. 1 w Sępólnie Krajeńskim = Morphological characteristics and physical fitness 7-years old children attending School No. 1 in Sępólno Krajeńskie - Mariusz Klimczyk; Wojciech Kędzierski (Kazimierz Wielki University, 2016)
Klimczyk Mariusz, Kędzierski Wojciech. Charakterystyka morfologiczna i sprawności fizycznej 7 - letnich dzieci uczęszczających do Zespołu Szkół nr. 1 w Sępólnie Krajeńskim = Morphological characteristics and physical fitness 7-years old children attending School No. 1 in Sępólno Krajeńskie. Journal of Education, Health and Sport. 2016;6(7):277-291. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57673 http://ojs.ukw.edu.pl/index.php/johs/article/view/3694       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 09.07.2016.     Charakterystyka morfologiczna i sprawności fizycznej 7 - letnich dzieci uczęszczających do Zespołu Szkół nr. 1 w Sępólnie Krajeńskim Morphological characteristics and physical fitness 7-years old children attending School No. 1 in Sępólno Krajeńskie   Mariusz Klimczyk, Wojciech Kędzierski   Uniwersytet Kazimierza Wielkiego w Bydgoszczy E-mail: Klimczyk1956@poczta.onet.p   Streszczenie             Celem pracy było określenie rozwoju somatycznego i sprawności fizycznej 7 - letnich dzieci. Badaniom zostały poddane dziewczęta i chłopcy. Uczniowie uczęszczają do ZSP. nr1 w Sępólnie Krajeńskim.   W szkole realizują zajęcia w wymiarze 21 godz. w tym z wychowania fizycznego 3 godz. tygodniowo. W pracy zastosowano następujące metody badań: eksperyment pedagogiczny, analiza literatury specjalistycznej, uwarunkowania morfologiczne zostały przebadane na podstawie pomiaru długości i masy ciała. Smukłość dzieci określona na podstawie wskaźnika Rohrera. Sprawność fizyczna mierzona była za pomocą testu Zuchory. Badania zostały przeprowadzone w odstępie sześciu miesięcy. Zastosowano następujące metody statystyczne: min i max wynik, średnia arytmetyczna, % zmian. Badania wykazały progres sprawności fizycznej i rozwoju fizycznego u chłopców i dziewcząt. Dziewczęta wykazały się lepszą sprawnością fizyczną.   Słowa kluczowe: rozwój fizyczny, sprawność fizyczna, motoryczność.   Summary The aim of the study was to determine somatic development and physical fitness 7 - year old children. The tests were subjected to girls and boys. Students attend the ZSP. No.1 in Sępólno Krajeńskie. In school classes perform in the dimension 21 hours. including physical education 3 hours. weekly. The study used the following test methods: pedagogical experiment, analysis of specialized literature, morphological conditions have been tested by measuring the length and weight. The slenderness of children determined based on the ratio Rohrer. Physical fitness was measured using the test Zuchora. Tests were conducted at an interval of six months. The following statistical methods: min and max result, the arithmetic mean,% change. The research have shown progress physical fitness and physical development in boys and girls. The girls showed a better physical fitness.   Keywords: physical development, physical fitness, motority.